EPCO-28. DOT1L AND PRC2 REGULATE A SHARED EPIGENETIC MECHANISM IN GLIOBLASTOMA AND MIXED LINEAGE LEUKEMIA. (14th November 2022) - Assaf, Samir; Bozek, Danielle; Luchman, H Artee; Weiss, Samuel
Abstract: Glioblastoma (GBM) is the most aggressive adult brain tumor, with a median survival of 15 months despite current treatments. We recently established that the epigenetic regulator Disruptor of Telomeric Silencing-1-Like (DOT1L) was essential for the growth of brain tumor stem cells (BTSCs), which are thought to underlie GBM tumor initiation and treatment resistance. Given the previously recognized importance of DOT1L histone methylation for the regulation of the similarly rare and aggressive childhood cancer, Mixed Lineage Leukemia (MLL), we interrogated for common mechanisms in both BTSCs and MLL cells, that overlap due to the epigenetic role of DOT1L. To gain a more detailed perspective of the importance of the DOT1L epigenetic mark in BTSCs, we performed a chemogenomic screen using the DOT1L inhibitor, EPZ-5676. Results from this screen revealed genes from transcriptional and epigenetic complexes required for a therapeutic response to DOT1L inhibition in BTSCs. Gene targeting approaches and growth assays further identified the Polycomb Repressive Complex 2 (PRC2) as a common determining factor for the growth response of both BTSCs and MLL cells following DOT1L inhibition. Furthermore, analysis of the chromatin accessibility changes regulated by DOT1L and PRC2 histone methylation identified both shared and unique epigenetic characteristics of GBM and MLL. The extent to which these shared mechanisms underpin the pathogenic process in these distinct diseases is being further investigated by assessing the divergence in transcriptional responses that emerge from this common epigenetic phenomenon. The findings from this study will provide insight into the importance of shared epigenetic mechanisms that underlie the tumorigenesis of unique cancers affecting the brain and blood.